Public support for the European car industry: An integrated analysis - Laura Grigolon; Nina Leheyda; Frank Verboven (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We provide an overview of public support for the European car industry during the past decade. First, we identify the most relevant instruments of public support, and review their economic assessment. The European Commission increasingly recognizes the role of economic analysis in controlling public aid to the car industry, although the degree of economic assessment varies across different instruments of public support and individual state aid cases. Moreover, the state aid legislative framework is open to derogations and interpretations. In particular, the Temporary Framework, approved by the Commission to tackle the last fi;nancial and economic crisis de facto implied a relaxation of the state aid rules and foresaw no formal control of individual state aids. Second, we aim to estimate the amount of public support for European car manufacturers. Three factors complicate the overall quantification of public support for each instrument: (i) the Commission does not scrutinize, and hence does not quantify all public support measures; (ii) the available information depends on whether the state aid is granted to individual companies or in the form of general schemes; and (iii) the available information depends on whether the aid is granted in the form of a grant, soft loan or guarantee. Our lower bound estimate of state aid suggests that the aid declined over the pre-crisis period, but peaked at exteuro1.2 billion as a response to the last financial and economic crisis in 2009. Perhaps even more strikingly, this state aid was combined with an unprecedented amount of public support granted through scrapping schemes of at least exteuro4.0 billion, and loans from the European Investment Bank of exteuro2.8 billion, or an equivalent of exteuro400 million of aid element. In conclusion, the existence of multiple public support instruments at different levels may create coordination problems and a lack of transparency, in spite of the Commission's efforts. The lack of transparency in turn poses a challenge for the quantification of state aid and non-state aid support to any industry or sector. This paper provides a first step towards informing the policy debate on the effects of public support to the car sector, and also stimulates the academic interest in the subject of state aid, and - more generally - public transfers to companies.
urn:nbn:de:bsz:180-madoc-326718
Keywords: 330; Subvention; Kraftfahrzeugindustrie; EU-Beihilfenkontrolle; Konjunkturpolitik; Wirtschaftskrise; EU-Staaten